C2-symmetric perylene-embedded double [5]helicenes - Swain, Asim; Rominger, Frank; Mastalerz, Michael (Organic letters, 2025)
High quantum yields and dissymmetry factors are key to enhancing the chiroptical properties of [n]helicene-functionalized polycyclic aromatic hydrocarbons for the development of circularly polarized materials. In a two-step synthesis, a C2-symmetric perylene-embedded double [5]helicene was obtained through Suzuki-Miyaura cross-coupling and base-catalyzed condensation. With a configurational stability of 23 kcal mol-1, the short-lived enantiomers were separated using chiral HPLC. Compared to pristine [5]helicene, the compound shows enhanced (chir)optical properties with a quantum yield of 0.7, a gabs of up to 8.8 × 10-3, and a glum of 0.7 × 10-3.